Open-distance education: quality delivery and learners' academic achievement at National Open University of Nigeria (2025)
The nature and delivery method of open-distance education has made it essential to continuously evaluate its quality. In light of this, the study explored how the quality of open distance education-specifically in terms of teaching and learning, course and program effectiveness, and assessment strategies-affects learners' academic success within the institution. The study employed a descriptive survey design. Purposive and Convenient sampling techniques were used for the selection of 200 learners made from the colleges of law, arts and social sciences, business and human resources, education, science and technology, as well as the center for continuing education, representing the population of learners in levels 100 to 500. We utilized the Open-Distance Education quality delivery and learners Academic Achievement Scale (r = 0.79) as the questionnaire for the study, which included thirty questions. Descriptive statistics and multiple regression analyses were conducted to evaluate the data. The research findings indicated that the quality of open-distance education delivery encompassing teaching and learning, course and program effectiveness, and assessment strategies explained 16.6% of the variation in students' academic achievement and had a noticeable impact on it (F (3.196) = 12.992; R2 = 0.166). The study s findings recommend that the management of the National Open University of Nigeria conduct regular evaluations to identify gaps or areas needing improvement. To uphold high academic standards, the distance learning institution should periodically assess its policies, systems, programs, facilities, and resources.